Rainfall initiation of debris flows in campania (italy): a two-phase analysis - fiorillo, Francesco; guadagno, Francesco M. (Italian journal of engineering geology and environment, 2011)
Debris flows in Campania begin as soil slides within the pyroclastic mantle that blankets the steep local hill slopes, which are, in turn, composed largely of carbonate bedrock. The historical pattern appears to be that clusters of debris avalanche- flows occur after intense rainstorms that follow an accumulation of a certain amount of pre-storm seasonal rainfall. Soil moisture appears to show a seasonal pattern of summer drying and winter wetting that is typical for the Mediterranean climate of the region. The physical analysis of the interaction of rainfall with the pyroclastic mantle requires two-phase approach. Phase 1, early in the rainfall season, concerns the accumulation of the retention water in the soils, up to field capacity, whereas the second phase of the analysis examines the accumulation of surplus moisture from intense rainfall, leading to the development of positive pore pressures and debris flow initiation. Rainfall data analysed cover also the last decade characterised by no debris-flow activity in the Sarno area